2022
DOI: 10.3390/s22030824
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Gait Parameters in Post Stroke and Parkinson’s Disease: A Comparative Study Using RGB-D Sensors and Optoelectronic Systems

Abstract: The accurate and reliable assessment of gait parameters is assuming an important role, especially in the perspective of designing new therapeutic and rehabilitation strategies for the remote follow-up of people affected by disabling neurological diseases, including Parkinson’s disease and post-stroke injuries, in particular considering how gait represents a fundamental motor activity for the autonomy, domestic or otherwise, and the health of neurological patients. To this end, the study presents an easy-to-use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 97 publications
(149 reference statements)
0
25
0
Order By: Relevance
“…In recent years, several studies have investigated the accuracy and effectiveness of Microsoft Kinect for the assessment of posture, gesture, lower limbs and gait performance in several pathological states, such as stroke, Parkinson's disease [26,[65][66][67][68][69][70] and other pathologies [71][72][73][74]. Different studies have reported its reliability for the assessment of spatiotemporal gait parameters (e.g., step length and gait speed) and kinematic variables (e.g., trunk angle) in healthy individuals, with results comparable to those of laboratorygrade systems [25,[75][76][77][78][79][80] using both the first and second model of the device. The last version of the device, the Azure Kinect DK, was released in 2019 and, thanks to its new body tracking algorithm based on deep learning and convolutional neural networks [81],…”
Section: Introductionmentioning
confidence: 92%
“…In recent years, several studies have investigated the accuracy and effectiveness of Microsoft Kinect for the assessment of posture, gesture, lower limbs and gait performance in several pathological states, such as stroke, Parkinson's disease [26,[65][66][67][68][69][70] and other pathologies [71][72][73][74]. Different studies have reported its reliability for the assessment of spatiotemporal gait parameters (e.g., step length and gait speed) and kinematic variables (e.g., trunk angle) in healthy individuals, with results comparable to those of laboratorygrade systems [25,[75][76][77][78][79][80] using both the first and second model of the device. The last version of the device, the Azure Kinect DK, was released in 2019 and, thanks to its new body tracking algorithm based on deep learning and convolutional neural networks [81],…”
Section: Introductionmentioning
confidence: 92%
“…For PoS, the sway of the body center of mass (COMBODY) is estimated from the skeletal model, as in [85,86,52], as the weighted average of the 3D centroids of some body segments, considering their mass and length as indicated by the anthropometric tables related to the anatomy of the human body [87]. For G, the estimated parameters are a subset of traditional spatio-temporal measures and arm swing parameters [56,58]: arm swing is a crucial element of walking and its impairment is often evident in individuals with PD.…”
Section: Objective Characterization Of the Motor Performancementioning
confidence: 99%
“…Optical approaches leverage video recording devices (e.g., cameras) and vision techniques to implement completely non-invasive and easily manageable solutions for tracking and analyzing human body movement. Several studies have proposed optical approaches to characterize upper limb motor function [52,53], analyze lower limb dysfunctions and postural control [54], estimate gait features [55,56], evaluate arms swing [57,58] and analyze balance disorders [59,60]. Optical approaches have also been widely used in motor rehabilitation for specific pathologies [61,62], including PD [15,63], due to their portability, versatility, high usability, and easy integration into virtual environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical applications, wearable sensors were used in several pathological states, such as stroke [ 4 , 5 , 6 ], obese [ 7 , 8 ], and elderly [ 9 ] patients; patients with lower limb amputation [ 10 ]; patients with Parkinson’s disease [ 4 , 11 , 12 ]; and patients hospitalized for knee joint rehabilitation [ 13 ]. In particular, wearable systems were used both to quantify the functional limitations of the patients, during several movements (gait [ 5 , 7 , 8 , 9 ], upper limb [ 6 , 11 ], time up and go test [ 10 ], and unconstraint activities at home [ 12 ]) and to evaluate their accuracy and precision in comparison with the gold standard [ 4 ]. These papers support the clinical usability of wearable technology for clinical movement assessment.…”
mentioning
confidence: 99%